THE EFFECT OF PHYSICAL RESILIENCE ON THE PERFORMANCE OF TRANSFERABLE LABOR (TKAD) DRIVERS AT BANK SUMUT MEDAN CENTER OFFICE - Andri Ekawati, Yuni; Suryana, Suryana (RADJA PUBLIKA, 2022)
This study aims to determine how much influence physical endurance has on the performance of Driver Outsourced Workers (TKAD) at PT. Bank Sumut Medan Head Office. The method used in this study is a quantitative method with several tests, namely reliability analysis , classical assumption deviation test and linear regression . Based on the results of the primary data regression which was processed using SPSS 18, the following multiple linear regression equation was obtained: Y = 0.934 + 0.020 + 0.991 + e . Partially, the general endurance variable (X1) has a positive but not significant effect on the performance of the Outsourced Workforce (TKAD) Driver PT. Bank Sumut Medan Head Office, as evidenced by the value of t count < t table (1.070 > 1.687). While the muscle endurance variable (X2) has a positive and significant influence on the performance of the Outsourced Workforce (TKAD) Driver PT. Bank Sumut Medan Head Office, as evidenced by the value of t count > t table (58,528 > 1,687). Simultaneously, the general endurance variable (X1) and muscle endurance (X2) have a positive and significant effect on the performance of the Outsourced Workforce (TKAD) Driver PT. Bank Sumut Medan Head Office. This means that the hypothesis in this study is accepted, as evidenced by the calculated F value > F table (2248 .802 > 3.25). The general endurance variable (X1) and muscle endurance (X2) were able to contribute influence on the performance variable by 99.2 % while the remaining 0.8% was influenced by other variables not examined in this study. From the conclusions above, the authors suggest that companies should pay more attention to the health of the Outsourced Workers (TKAD), especially drivers so that their health is maintained by providing health and safety guarantees by covering all hospital costs and medicines when they are sick.